Parametric Analysis of Outrigger Systems for High-Rise Buildings with Different Geometric Shapes - Giulia Angelucci; Edoardo Cecca; Fabrizio Mollaioli (Applied Sciences)
The increasing demand for efficient lateral load-resisting systems in high-rise construction necessitates the investigation of advanced structural solutions. Among many alternatives, outrigger systems are widely acknowledged as effective supplementary schemes for enhancing the strength and stability of tall buildings subjected to lateral loads. This work investigates whether the potential of such systems, well established for regular structures, also remains valid for the complex-shaped geometries that often characterize contemporary tall buildings. Tilted and twisted geometries are explored via the parametric variation of tilt and twist angles. The structural response, both with and without outriggers, is evaluated and compared to that of a regular geometry. The number, location, and relative stiffness of outriggers with respect to the inner core are also systematically varied to provide a comprehensive assessment. To facilitate the extensive parametric analysis, simplified analytical models are employed. Then, a selection of representative geometries are utilized to generate refined three-dimensional numerical models. A comparative survey between these two modeling approaches elucidates the accuracy and limitations of simplified methodologies, while providing insights into the structural behavior of outrigger systems. This work underscores the critical interaction between building configuration, outrigger location, and flexural stiffness in optimizing high-rise structural performance. The results reveal a significant influence of the building’s morphology on the structural response, with major improvements exhibited by regular and tilted configurations. Conversely, twisted geometries can considerably alter global structural behavior depending on their degree of twist, potentially diminishing the outrigger’s efficacy in mitigating lateral displacement and core base moment demands. By providing quantifiable insights into outrigger performance in complex-shaped structures, this research guides a more integrated architectural and structural approach in contemporary high-rise construction, leveraging an efficient simplified modeling framework for preliminary design.